Correlation between serum vitamin D level and acute invasive enteritis in children - Lingrong Yang; Yu Fang; Jinyu Zheng; Qiaoying Zhu; Li Tang; Fu Xiong (Immunity, Inflammation and Disease)
Abstract Background Diarrhea is a leading cause of death in young children worldwide. Vitamin D deficiency impairs the body's ability to clear pathogens, reduces tight junction protein expression in intestinal epithelial cells, and enhances Th1‐mediated intestinal inflammation. This study aimed to investigate the effects of serum vitamin D levels on acute invasive enteritis in children. Methods This prospective cohort study included 82 children aged 1–3 years with clinically diagnosed acute invasive enteritis at Sichuan Maternal and Child Health Hospital from February 2021 to February 2022, alongside a control group of 80 healthy children. Fecal specimens were collected for routine tests and occult blood analysis, while blood samples were taken for routine tests, C‐reactive protein, and 25‐OHD levels. Comparative analyses were performed between groups, and multifactorial logistic regression was used to identify factors influencing invasive enteritis. Results The study group showed significantly lower serum 25‐OHD levels (27.95 ± 9.91 ng/mL) compared to controls (32.76 ± 10.23 ng/mL, p < .01). Among the study group, 19.5% (16/82) had levels <20 ng/mL, versus 12.5% (10/80) in controls. Regular vitamin D supplementation was lower in the study group (58.5% vs. 77.5%, p < .05). Outdoor activity duration was also reduced (2.57 ± 0.98 h vs. 3.04 ± 0.88 h, p < .01). Multivariate analysis identified that exclusive breastfeeding, greater outdoor activity time and regular vitamin D supplementation were all associated with reduced risk of invasive enteritis (p < .05). Conclusion The findings indicate an association between low serum 25‐OHD levels and acute invasive enteritis in children aged 1‐3 years, suggesting that consistent vitamin D supplementation and sufficient outdoor activity may protect against this condition.